Proof-of-concept of a prior validated LC-MS/MS method for detection of N-lactoyl-phenylalanine in dried blood spots before, during and after a performance diagnostic test of junior squad triathletes - Bauhaus, H.; Möller, T.; Keller, S.; Thomas, A.; Braun, H.; Wahl, P.; Thevis, M. (Frontiers in Sports and Active Living, 2025)
IntroductionN-lactoyl-phenylalanine (lac-phe) is an exercise-inducible metabolite that is discussed for suppressing appetite. As no point-of-care lac-phe analysis for frequent sample collection during exercise exists, the objectives of this study were (1) to develop and validate a method for quantifying lac-phe by liquid chromatography tandem mass spectrometry (LC-MS/MS) using 20 µl of capillary blood collected on cellulose-based dried blood spot (dbs) cards (QIAcard® FTA® DMPK-C) and (2) to determine lac-phe dbs concentrations before, during, and after a combined running and cycling performance test protocol in regional junior squad triathletes for proof-of-concept.MethodsThe validated method (precision <8%, accuracy <7% in a working range of 0–100 ng/ml, stability >28 days at −20°C and 20°C) was successfully applied in a combined running and cycling performance diagnostic test. Dbs samples were collected by trained researchers at multiple time points – before, during, and after the performance diagnostic test - from 15 female and male junior squad triathletes on two test occasions separated by 3 months and a training period.ResultsLac-phe concentrations increased from 31.5 ± 10 nmol/L at baseline to a maximum of 101.0 ± 40.1 nmol/L at time-to-exhaustion after the second incremental test. 15 min after exercise, lac-phe concentration decreased to 89.7 ± 30.4 nmol/L. No statistical difference between the two test occasions was seen. Sex-specific differences were observed, with female subjects showing significantly higher lac-phe concentrations than male subjects (p < 0.05) at time-to-exhaustion after the first incremental test and at the onset of the second incremental test. No statistically significant correlations were identified between lac-phe and lactate, glucose as well as anthropometric and respiratory parameters.ConclusionThis study introduces a robust method that, for the first time, enables the quantification of lac-phe concentrations not only before and after, but also during a performance test. By applying this approach, it contributes novel insights into the temporal dynamics of exercise-induced alterations in lac-phe concentrations in humans.